2020
DOI: 10.3390/ijerph17249436
|View full text |Cite
|
Sign up to set email alerts
|

Body Acceptance by Pregnant Women and Their Attitudes toward Pregnancy and Maternity as Predictors of Prenatal Depression

Abstract: Background: Depressive symptoms during pregnancy may cause unfavorable consequences for both the mother and the infant’s physiological and psychological health. Recent evidence indicates that body image plays an important role in prenatal depression. The present study’s main purpose was to investigate the level of acceptance of physical appearance in pregnant women, their attitudes toward pregnancy and maternity, and some obstetric characteristics as significant predictors in the development of depression. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
7

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
3
10
0
7
Order By: Relevance
“…In this regard, it represents progress in the in-depth understanding of the relationships between existing conventional gender norms and the impossibility of traditional parenting that may modulate mental health in expectant mothers in perinatal stages. In line with previous studies, the present study also showed that some clinical factors—such as previous pregnancies—interfered with the means of gender norm conformity in women undergoing treatment [ 18 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In this regard, it represents progress in the in-depth understanding of the relationships between existing conventional gender norms and the impossibility of traditional parenting that may modulate mental health in expectant mothers in perinatal stages. In line with previous studies, the present study also showed that some clinical factors—such as previous pregnancies—interfered with the means of gender norm conformity in women undergoing treatment [ 18 , 28 , 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…The aspects related to romantic relationships and thinness and their relationship with quality of life in the relational subscale stand out, especially in the sample of women in treatment who presented lower levels of quality of life related to these factors. These factors are closely linked to mental illness, such as postpartum depression, anxiety, or other [ 29 , 31 ]. This confirms the need for health and follow-up itineraries that coordinate ART Units with mental health, reproductive, and primary care staff.…”
Section: Discussionmentioning
confidence: 99%
“…Gebelik süreci; kadınlar için genellikle olumlu hisler uyandıran fakat beden imajının negatif etkilenmesiyle ambivalan duygular yaşatan bir zaman dilimidir. Kitlesel iletişim araçları tarafından ideal vücut imajı mesajının yanlış şekilde verilmesi bu süreçteki lohusaların ambivalan duygularının daha karmaşık hale gelmesine, beden memnuniyetsizliğine, benlik saygısının azalmasına ya da depresif belirti göstermesine neden olabilmektedir (13). Bu araştırmanın dikkat çeken ilk bulgusu da; BKİ'nin bedensel memnuniyetle direkt ilişkili olduğu ve normalden fazla kiloya sahip lohusaların olumsuz emosyonel duygular yaşadığıdır.…”
Section: Discussionunclassified
“…Mental health disorders affect many women during pregnancy and the postpartum period ( 3 , 8 , 9 ). Low self-esteem, depressive symptoms, and low levels of body appreciation during pregnancy and postpartum can have negative consequences for the well-being of the woman, her partner, and her family, and for the birth and development of the child ( 10 ). In particular, ~30–70% of women who have given birth have had lower self-esteem after delivery ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, pregnancy and postpartum can intensify or cause a negative relationship with the body ( 1 , 3 ). Recently, authors reported on the importance of evaluating body dissatisfaction during pregnancy as a predictor of the onset of prenatal depression in Polish women ( 10 ). However, the authors pointed out that, in clinical practice, this risk factor should be considered in combination with positive maternal attitudes, not separately ( 10 ).…”
Section: Introductionmentioning
confidence: 99%